Intratumoural Treatment of 18 Cytologically Diagnosed Canine High-Grade Mast Cell Tumours With Tigilanol Tiglate - Brown, Graham K.; Campbell, Justine E.; Jones, Pamela D.; De Ridder, Thomas R.; Reddell, Paul; Johannes, Chad M. (Frontiers in Veterinary Science, 2021)
Canine high-grade mast cell tumours (HGMCT) are associated with a poor prognosis, are inherently more invasive, and have higher rates of local recurrence. The primary aim of this retrospective study was to assess the efficacy of intratumoural tigilanol tiglate (TT) as a local treatment option. Eighteen dogs with mast cell tumours (MCT) cytologically diagnosed by veterinary pathologists as either high-grade or suspected high-grade MCT were treated with TT. The TT dose was based on tumour volume (0.5 mg TT/cm3 tumour volume) and delivered intratumourally using a Luer lock syringe and a fanning technique to maximise distribution throughout the tumour mass. Efficacy was assessed on the presence/absence of a complete response (CR) to therapy at days 28 and 84 using response evaluation criteria in solid tumours (RECIST). For dogs not achieving a complete response after 28 days, the protocol was repeated with a second intratumoural TT injection. Ten out of 18 dogs (56 %) in this study achieved and maintained a complete response to at least 84 days after their first or second treatment. Six patients were alive and available for evaluation at 2 years, 3 of those were recurrence free, and a further 3 patients were recurrence free following a second treatment cycle. Tigilanol tiglate shows efficacy for local treatment of HGMCT, with higher efficacy noted with a second injection if CR was not achieved following the first treatment. In the event of treatment site recurrence, the tumour may be controlled with additional treatment cycles. Tigilanol tiglate provides an alternative local treatment approach to dogs with HGMCT that would either pose an unacceptable anaesthetic risk or the tumour location provides a challenge when attempting surgical excision.